2018
DOI: 10.1063/1.5055250
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth doping and effective band-convergence in SnTe for improved thermoelectric performance

Abstract: Thermoelectric performance of SnTe has been found to enhance with isovalent doping of alkaline and transition metal elements where most of these elements have solubility of less than 13%. We propose a strategy of doping rare earth element Yb to enhance the thermoelectric performance of SnTe. With heavy atomic mass and strong spin-orbit coupling, even the mild doping of Yb (~ 5%) is enough to create a degeneracy via band-convergence which enhances the density of states near Fermi level and improve overall perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…[19][20][21][22]3,[23][24][25][26][27][28]6,29,30 Further, the superionic CT2 has an interesting structure where the tellurium atom forms a rigid sublattice and the liquid-like Cu ions are distributed randomly in the rigid sublattice and thus classified as PLEC. 31 It has been observed that several state of the art TE materials are tellurides, such as PbTe, SnTe, 32,4,5 and Bi 2 Te 3 , 14,15 and have better performances than their Se and S counterparts. 24,25,8 Thus, the present work focuses on the Raman spectroscopic studies of copper tellurides.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22]3,[23][24][25][26][27][28]6,29,30 Further, the superionic CT2 has an interesting structure where the tellurium atom forms a rigid sublattice and the liquid-like Cu ions are distributed randomly in the rigid sublattice and thus classified as PLEC. 31 It has been observed that several state of the art TE materials are tellurides, such as PbTe, SnTe, 32,4,5 and Bi 2 Te 3 , 14,15 and have better performances than their Se and S counterparts. 24,25,8 Thus, the present work focuses on the Raman spectroscopic studies of copper tellurides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, the strategies to enhance zT are based on a phonon–glass–electron–crystal (PGEC) approach where a crystalline semiconducting materials is desirable for high σ (electron–crystal) and disordered atomic arrangements are needed for low κ (phonon–glass) . To achieve high power factor ( S 2 σ ), various materials with high crystal symmetry, multiple valleys near the Fermi level through insertion of resonant levels, convergence of multiple valence bands, and doping of heavy elements with small electronegativity differences of constituent elements have been explored. On the other hand, strategies such as exploring complex crystal structure, , alloying, ,, solid solutions, ,, rattling atoms, , nanostructuring, , and acoustic phonon scattering through optical phonons are utilized to reduce κ.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity (κ) has contributions from the electronic (κ e ) and lattice (κ L ) components. Current state-of-the-art TE materials such as Bi 2 Te 3 and PbTe that have found commercial applications are expensive and toxic. Thus, efforts are underway to find environmental friendly and cheaper alternative materials.…”
Section: Introductionmentioning
confidence: 99%
“…Even a minimal amount of doping ($5%) with rare earth material Yb causes effective band convergence and increases DOS near Fermi level in SnTe. 241 SnTe/PbSe, SnTe/PbS, EuTe/PbTe superlattices and SnEuTe lms also show better thermoelectric properties than bulk SnTe. 110 Wu et al 242 reported a ZT $ 0.7 at 675 K in an AgPb 9 -Sn 9 SbTe 20 sample fabricated by MA and plasma-activated sintering (PAS) technique.…”
Section: Sn Chalcogenides As Te Materialsmentioning
confidence: 99%